Multinational Oil Companies and Corporate Social Responsibility: A Case Study of Oil Companies in Nigeria - Otuekong, Iniobong Out (2009)
This study primarily addresses the subject of Corporate Social Responsibility (CSR) as carried out by Multinational Oil Companies (MOCs). The need for involvement of these MOCs in the development of their operational environment cannot be overstressed considering the enormous negative impact caused by their exploration and exploitation activities. The field work was carried out in Port Harcourt and seven other communities in Rivers State. The instrument used for data collection was interviews, focus group discussions and personal observation. The analysis of the data collected indicates that (i) the MOCs have been involved in carrying out social responsibilities in their host communities to a certain extent (ii) the MOCs as part of their contribution to the development of their host communities, have helped in building of schools, hospitals, road networks, award of scholarship to eligible indigenes as well as provide boreholes, but that the host communities want sustainable economic, social and environmental development projects (iii) the internal factors impinging on the implementation of social responsibility activities include youth restiveness, corruption, lack of support by shareholders, reduction of profit margin, diversion of attention from real business and creation of excessive cost (iv) the operations of the MOCs impacts negatively on the host communities causing pollution in terms of oil spillage and gas flaring (v) the crisis in the Niger Delta, manifesting in armed violence and kidnappings reflect the frustration of the people of the region, who have been complaining for years of; the mismanagement of rents from their natural resources, environmental damage from oil exploration, perpetually rising unemployment, increasing poverty as well as lack of infrastructural development in the region. It was therefore recommended that (i) MOCs should be of good conscience as to observe the basic rule of „give and take ‟ (ii) the government should on their part institute stern measures that will ensure compliance with environmental laws and inject discipline into the industry (iii) MOCs should hire external consultants and independent auditors for the execution of contracts (iv) MOCs should develop jobs, provide grants as well as loans to the residents of the communities as this will help in the provision of a means of livelihood for the residents and finally that MOCs should embrace social responsibility and tackle them with the tenacity deserved of them.